Chaperonin-Dependent Accelerated Substitution Rates in Prokaryotes - Bogumil, David (Oxford University Press, 2010)
Many proteins require the assistance of molecular chaperones in order to fold efficiently. Chaperones are known to mask the effects of mutations that induce misfolding because they can compensate for the deficiency in spontaneous folding. One of the best studied chaperones is the eubacterial GroEL/GroES system. In Escherichia coli, three classes of proteins have been distinguished based on their degree of dependency on GroEL for folding: 1) those that do not require GroEL, 2) those that require GroEL in a temperature-dependent manner, and 3) those that obligately require GroEL for proper folding. The buffering effects of GroEL have so far been observed in experimental regimens, but their effect on genomes during evolution has not been examined. Using 446 sequenced proteobacterial genomes, we have compared the frequency of amino acid replacements among orthologs of 236 proteins corresponding to the three categories of GroEL dependency determined for E. coli. Evolutionary rates are significantly correlated with GroEL dependency upon folding with GroEL dependency class accounting for up to 84% of the variation in amino acid substitution rates. Greater GroEL dependency entails increased evolutionary rates with GroEL obligatory proteins (Class III) evolving on average up to 15% faster than GroEL partially dependent proteins (Class II) and 35% faster than GroEL-independent proteins (Class I). Moreover, GroEL dependency class correlations are strictly conserved throughout all proteobacteria surveyed, as is a significant correlation between folding class and codon bias. The results suggest that during evolution, GroEL-dependent folding increases evolutionary rate by buffering the deleterious effects of misfolding-related mutations.